Biomass-derived carbon nanostructures and their applications as electrocatalysts for hydrogen evolution and oxygen reduction/evolution - Maliutina, Kristina Mikhailovna; Omoriyekomwan, Joy Esohe; He, Chuanxin; Fan, Liangdong; Folli, Andrea (Frontiers in Environmental Engineering, 2023)
Biomass derived electrocatalysts with rationally designed activity, selectivity, and stability present a major sustainable approach for the electrochemical production of fuels and value-added chemicals. This review presents recent advances in the field of biomass-derived electrocatalytic nanostructures for the hydrogen evolution reaction (HER) and the oxygen reduction and evolution reactions (ORR and OER) , that are subject of major research efforts, as well as public and private investment, as they will play a crucial role in the energy transition and in achieving net zero carbon emissions. The review summarises experimental and theoretical investigations aiming at tuning electrocatalytic performances of sustainable C-based nanostructured materials, and present opportunities for future commercialization of innovative energy materials and applications. In reviewing relevant literature in the field, we focus on the correlation between electrocatalytic activity/selectivity and synthesis methods, composition, physical chemical characteristics, in the attempt to uncover a clear structure-activity relationship. Furthermore, this study provides a critical comparison of the different electrocatalysts in light of their catalytic mechanisms, limiting phenomena, and practical applications for sustainable future technologies.